Enhancing the Environmental Impact Assessment for the Foreign Direct Investment Regime in Vietnam: an Analysis from Integration Perspective - Tran Viet Dung (Universitas Airlangga, 2019)
Foreign direct investment (FDI) plays an important role in the economic growth of Vietnam, contributing to nearly 22 per cent of the GDP. To attract FDI the government has committed to promoting investment climate and ensuring FDI protection under various international arrangements. FDI inflows into the manufacturing and processing sectors have seen a strong increase after Vietnam’s successful accession to the WTO. However, FDI also contributes to various environmental problems and challenges in Vietnam. From 2008 to 2017, most serious environmental disputes related to manufacturing activities were caused by FDI enterprises. The sanctions against FDI enterprises, however, may jeopardise the state’s responsibilities under investment protection treaties. One of the few realistic approaches to strengthening the environmental management of FDI is to promote the participation of the public in the environmental risk assessment and amend the investment treaties to regulate the issue of environment management. This study will adopt an integrative approach by integrating the rules and principles of environmental management into the FDI regime of Vietnam.